2013
DOI: 10.1007/s12603-013-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fasting and Calorie Restriction (FCR) on mood and depression among ageing men

Abstract: Our findings show that a FCR dietary regime is effective in improving mood states and nutritional status among ageing men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 20 publications
3
72
1
4
Order By: Relevance
“…Among participants of the Chicago Health and Aging Project, for instance, researchers reported an energy intake of 1,500 ± 573 kcal in the lowest tertile of Mediterranean Diet Score (MedDietScore) and 1,945 ± 578 kcal in the upper tertile, which had lower annual depression rates (Skarupski, et al, 2013). A 3-month clinical trial testing the effects of fasting and moderate calorie restriction in 32 healthy Malay men, aged 50 to 70 years, found no significant differences in depression scores (Hussin, Shahar, Teng, Ngah, & Das, 2013). The higher overall energy intakes in our study may reflect a higher energy expenditure, possibly due to higher physical activity potentially due to better health (J. J.…”
Section: Discussionmentioning
confidence: 51%
“…Among participants of the Chicago Health and Aging Project, for instance, researchers reported an energy intake of 1,500 ± 573 kcal in the lowest tertile of Mediterranean Diet Score (MedDietScore) and 1,945 ± 578 kcal in the upper tertile, which had lower annual depression rates (Skarupski, et al, 2013). A 3-month clinical trial testing the effects of fasting and moderate calorie restriction in 32 healthy Malay men, aged 50 to 70 years, found no significant differences in depression scores (Hussin, Shahar, Teng, Ngah, & Das, 2013). The higher overall energy intakes in our study may reflect a higher energy expenditure, possibly due to higher physical activity potentially due to better health (J. J.…”
Section: Discussionmentioning
confidence: 51%
“…The second randomized controlled trial of fasting was reported in 3 articles using the primary endpoints of "mood states and depression status" (34), "metabolic parameters and DNA damage" (35), and "mood and quality of life" (33). One of these articles was published before full enrollment in the trial (33), used similar outcomes as one of the other articles (34), and will not be discussed.…”
Section: Evidence Of a Fasting Benefit For Humans Based On Surrogate mentioning
confidence: 99%
“…Overall mood-including components from tension, anger, and confusion-was improved by fasting in a study of 32 subjects during 12 wk of the intervention phase. Unfortunately, correction for the 7 hypothesis tests of measures of mood was not done and would result in no finding being statistically significant (34). From the same 12-wk trial but in another article, blood pressure, total cholesterol, LDL cholesterol, weight, fat mass, and other factors-including DNA damage measures-were changed by fasting (35).…”
Section: Evidence Of a Fasting Benefit For Humans Based On Surrogate mentioning
confidence: 99%
See 1 more Smart Citation
“…Mood improvement that occurs during these first few days of fasting could be a direct consequence of this activation. In clinical studies, fasting is frequently accompanied by increased vigilance and mood-enhancement, a subjective feeling of well-being, and sometimes even a feeling of euphoria [53,112,113,114,115,116]. …”
Section: Clinical Effects Of Fastingmentioning
confidence: 99%